THE LEVELS OF QUESTIONS USED IN THE ENGLISH TEXTBOOK ENTITLED “STOP BULLYING NOW”FOR THE XI GRADE OF SENIOR HIGH SCHOOL - Wahyuni, Ketut Budi (Universitas Pendidikan Ganesha, 2021)
Reading comprehension in Indonesian students is very weak. It is proven by Pisa 2018, a result which states that from a comparison between science, mathematics, and reading comprehension, Indonesian students are ranked 74th in the sixth from bottom. This article aims to analyze the level of questions used in an English textbook entitled